PERALUMINOUS GRANITES FREQUENTLY WITH MANTLE-LIKE ISOTOPE COMPOSITIONS: THE CONTINENTAL-TYPE MURZINKA AND DZHABYK BATHOLITHS OF THE EASTERN URALS - Gerdes A.; Montero P.; Bea F.; Fershater G.; Borodina N.; Osipova T.; Shardakova G. (My University, 2002)
Murzinka and Dzhabyk are continental-type batholiths of the middle and southern East Uralian domain. They comprise mainly undeformed peraluminous K-rich granites whose elemental composition is similar to some late-Variscan granites of western Europe, but with much more primitive Sr and Nd isotope ratios. Murzinka (254±5 Ma) is composed of silica-rich granites forming two different rock series with a 87Sr/86Srinit of 0.709 and 0.704, respectively. Both series have enormous variations in εNd255 (-11.9 to -0.1 and -8.9 to +4.1) that reveal derivation from heterogeneous sources. Dzhabyk (291±4 Ma) also comprises two coeval magmas which yielded voluminous granites and quartz-monzonites, respectively, with smaller differences in 87Sr/86Srinit and εNd290 (~0.7043, +0.8 to +1.6 and ~0.7049, 0.0 to +0.8). Despite their isotope compositions both batholiths lack evidence of genetic involvement of a mantle-derived parental magma. Moreover, we suggest that Dzhabyk granitoids were generated by polybaric partial melting of Paleozoic island-arc material, whereas Murzinka granitoids derived from an extremely heterogeneous source consisting mainly of Paleozoic and Proterozoic metagreywackes. This implies a relative fast reworking of juvenile arc crust and burial of the protoliths during the orogenic evolution of the Urals. Since there is neither evidence of significant extension, nor a direct link with subduction, we suggest that the main cause for late-orogenic anatexis was elevated heat production and fertility in the protolith, perhaps combined with some additional heat from unexposed mafic intrusions.